Journal of Applied Informatics and Technology (Full Issue): Vol. 5 No. 1 (2023): January-June - Editor, Journal of Applied Informatics and Technology (Journal of Applied Informatics and Technology, 2023)
Contents - Forecasting Fall-Out of Undergraduates Pibulsongkram Rajabhat University with Data Mining Technique (pp. 1-17) - Classifying Nail Abnormalities by Convolutional Neural Network (pp. 18-35) - Developing a System for Notification of Forgetting to Close the Dormitory Door with Mobile Application using Internet of Things (pp. 36-50) - A Study of Areas Affected by the Burning of Waste Landfills in Samut Prakan Province with the ALOHA Model (pp. 51-59) - Integrated of Geographic Information System for Supporting Tourism 12 Cities Hidden Gems Plus: Case Study Eastern Region (pp. 60-70) - The Development Application Promote Agritourism of Pakdee Farm with Augmented Reality Technology (pp. 71-85)